Occupational Stressors and Job Satisfaction among Royal Malaysian Navy at Teluk Sepangar Sabah: Comparison between Submariners and Surface Ship Personnel - Mohd Shahnaz Shamsuddin; Fredie Robinson; Safirah Jaan Jaafar; Syed Shajee Hussain; Than Myint (Universiti Malaysia Sabah, 2021)
Introduction: In the military, different aspects of job satisfaction are taken into account as compared to the civilian workforce. Some of the job satisfaction is related to as the working environment, nature of work and task, military operations and organizational traditions (e.g. obedience, policies and military disciplines). All these job stressors have an influence on the job satisfaction. Therefore, the military cannot be regarded as a normal and traditional work setting. The objectives of this study were to determine the differences of occupational stressors among submariners and surface ship personnel, the job satisfaction itself and to find a relationship between job satisfaction and occupational stressors among those two groups of occupation. Methods: In this cross-sectional comparative study, self-administered NIOSH (USA) Generic Job Stress Questionnaire was used as a tool to measure occupational stressors and job satisfaction among 50 submariners and 48 surface ship personnel. Results: The response rate was 98%. The result showed that there are statistically significant difference in the means in terms of job stressors among submariners and surface ship crews except for the conflict at work (P=0.03) and job requirement (P=0.01). Simple linear regression analysis shows that only mental demands had significant relationship with job satisfaction (P<0.001). Other job stressors such as the physical environment which were very different between these two occupations did not show any significant association on the occupational stress and job satisfaction when compared. Conclusion: Further study would hope to examine the mental demand aspect as this can improve the overall job satisfaction level among these two groups of occupation.